Repeated exposure to 4-methyl-2, 4-bis(4-hydroxyphenyl)pent-1-ene (MBP) accelerates ligand-independent activation of estrogen receptors in long-term estradiol-deprived MCF-7 cells. (1st April 2023) - Hirao-Suzuki, Masayo; Takiguchi, Masufumi; Yoshihara, Shin'ichi; Takeda, Shuso
Abstract: It was previously identified that there may be an active metabolite of bisphenol A (BPA), 4-methyl-2, 4-bis(4-hydroxyphenyl)pent-1-ene (MBP). An in vitro system was developed to detect MBP toxicity to the Michigan Cancer Foundation-7 (MCF-7) cells that had been repeatedly exposed to a low dose of the metabolite. MBP profoundly activated estrogen receptor (ER)-dependent transcription as a ligand, with an EC50 of 2.8 nM. Women are continuously exposed to numerous estrogenic environmental chemicals; but their susceptibility to these chemicals may be significantly altered after menopause. Long-term estrogen-deprived (LTED) cells, which display ligand-independent ER activation, are a postmenopausal breast cancer model derived from MCF-7 cells. In this study, we investigated the estrogenic effects of MBP on LTED cells in a repeated exposure in vitro model. The results suggest that i) nanomolar levels of MBP reciprocally disrupt the balanced expression of ERα and ERβ proteins, leading to the dominant expression of ERβ, ii) MBP stimulates ERs-mediated transcription without acting as an ERβ ligand, and iii) MBP utilizes mitogen-activated protein kinase and phosphatidylinositol-3 kinase signaling to evoke its estrogenic action. Moreover, the repeated exposure strategy was effective for detecting low-dose estrogenic-like effects caused by MBP in LTED cells. Highlights: ● A bisphenol A metabolite, MBP, activates endocrine-resistant LTED cells. ● Repeated exposure methodology enables us to detect low-dose effects of MBP. ● MBP disrupts the balanced expression of ERα/β proteins, which leads to dominant ERβ. ● MBP stimulates ERs-mediated transcription without acting as a ligand for ERβ. ● MBP utilizes both MAPK and PI3K signaling to elicit ERβ-driven estrogenic action.